2011
DOI: 10.1186/1471-2156-12-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence polymorphisms within the bovine guanine nucleotide-binding protein Gs subunit alpha (Gsα)-encoding (GNAS) genomic imprinting domain are associated with performance traits

Abstract: BackgroundGenes which are epigenetically regulated via genomic imprinting can be potential targets for artificial selection during animal breeding. Indeed, imprinted loci have been shown to underlie some important quantitative traits in domestic mammals, most notably muscle mass and fat deposition. In this candidate gene study, we have identified novel associations between six validated single nucleotide polymorphisms (SNPs) spanning a 97.6 kb region within the bovine guanine nucleotide-binding protein Gs subu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 87 publications
(97 reference statements)
0
24
0
Order By: Relevance
“…These did not overlap with most markers previously detected as associated with gestation length (Maltecca et al , 2009; 2011) in dairy cattle, although Maltecca et al (2011) identified 6 SNP on BTA3. Some SNP in imprinted domain regions on BTA13 were associated with calving difficulty and gestation length of dairy cows (Sikora et al , 2011). A similar region was identified on BTA21 (beginning at BTA21:68.1 Mb; Magee et al , 2010) including delta-like 1 homolog DLK1 and deiodinase, iodothyronine, type III ( DIO3 ); this region was associated with various traits in dairy cattle, including gestation length (Magee et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…These did not overlap with most markers previously detected as associated with gestation length (Maltecca et al , 2009; 2011) in dairy cattle, although Maltecca et al (2011) identified 6 SNP on BTA3. Some SNP in imprinted domain regions on BTA13 were associated with calving difficulty and gestation length of dairy cows (Sikora et al , 2011). A similar region was identified on BTA21 (beginning at BTA21:68.1 Mb; Magee et al , 2010) including delta-like 1 homolog DLK1 and deiodinase, iodothyronine, type III ( DIO3 ); this region was associated with various traits in dairy cattle, including gestation length (Magee et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In cattle, two SNPs in GNAS complex locus have been associated with reproductive traits (Sikora et al. ). One of them was associated with direct calving difficulty due to the size of offspring and gestation length, while the other with maternal calving difficulty (Sikora et al.…”
Section: Resultsmentioning
confidence: 99%
“…; Khatib ; Sikora et al. ). Recently, paternal imprinting of NESP55 – one of the GNAS transcripts – was confirmed in pigs (Oczkowicz et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, bovine imprinted gene orthologs have now been comprehensively shown to regulate economically important production traits in cattle (Magee et al 2010a,b;Sikora et al 2011). However, although similar epigenetic regulatory mechanisms also may affect health traits (Chao & D'Amore 2008) and exciting results are emerging in other species, the stability, heritability and association between epigenetic marks in immune genes and health traits in cattle have yet to be conclusively established.…”
Section: Current Challenges For Epigenetics Researchmentioning
confidence: 96%